New development: The behavioural effects of risk management in higher education. Issue 6 (18th August 2022) - Narayan, Anil K.; Kommunuri, John
IMPACT: This article will be useful to policy-makers and managers to gain control over risk-taking behaviour in higher education institutions (HEIs). It provides an understanding of often overlooked psychological hurdles. The article assists policy-makers and managers in formulating sound risk management policies and frameworks. In addition, it builds a risk-awareness culture showing how to avoid behavioural pitfalls and over-ambitious target-setting that is putting many HEIs under extreme financial risk ABSTRACT Risk management is gaining increasing importance in the higher education sector, but risk-taking behaviours associated with human vulnerabilities are not well understood. This article offers new insights into people's risk-taking behaviour and the consequences for higher education institutions. The authors discuss core psychological and socio-cultural issues associated with behavioural risk management and propose ideas to help overcome risk-taking behavioural problems.